Combined Starter Phosphorus and Manure Applications on Silage Corn Yield and Phosphorus Uptake in Southern BC - Messiga, Aimé J.; Lam, Camellia; Li, Yunkun; Kidd, Steven; Yu, Shaobing; Bineng, Carine (Frontiers in Earth Science, 2020)
Phosphorus (P) management using mineral and manure P in excess of plant needs contributes to legacy soil P in coastal British Columbia, Canada. The objectives of this study were (a) to assess the effects of starter P at early growth stages and their carryover through corn maturity, and (b) to determine how corn yields relate to soil P saturation indicators. Eleven 1-year experiments were conducted on sites with contrasting legacy soil P in 2018 (three sites) and 2019 (eight sites). Six combinations of starter and manure P rates (T1: 0Pstarter + 0Pmanure; T2: 0Pstarter + 35Pmanure; T3: 5Pstarter + 30Pmanure; T4: 10Pstarter + 25Pmanure; T5: 15Pstarter + 20Pmanure; T6: 20Pstarter + 15Pmanure) were assigned to a RCBD with four replicates. In 2018, corn dry matter weight (DMW) at the 6-leaf stage was affected by starter P in all sites, and the response curve was described by a linear-plus-plateau model with critical starter P of 5 and 7.5 kg ha 1. In 2019, corn DMW at early growth stages was not affected by starter P. Corn DMW at harvest varied between 15.15 Mg ha–1 in sites with low initial soil P and 27.20 Mg ha–1 in sites with excess P. Four sites exhibited a trend of high DMW with treatment comprising low starter P and high side-dressed manure P additions. The degree of P saturation (DPS, 14% to 38%) and P saturation index (PSI, 3% to 14%) were related to corn DMW by quadratic functions (R2 = 0.76 - 0.94). From these results, we can conclude that the effect of starter P on young corn plants varies with year, but does not carryover through harvest. Moreover, current starter P (30 - 40 kg ha–1) recommended for corn can be reduced by up to 75% (5 - 7.5 kg ha–1) without affecting yield, thus reducing annual P inputs and farmers’ production costs. Finally, PSI as a proxy of DPS is a possible agro-environmental indicator that, coupled with reduced starter P fertilizer, can further contribute to reducing the risk of P transfer from agricultural soils in coastal British Columbia.